Self‐reported personality traits are prospectively associated with proxy‐reported behavioral and psychological symptoms of dementia at the end of life. (4th September 2017) - Sutin, Angelina R.; Stephan, Yannick; Luchetti, Martina; Terracciano, Antonio
Abstract : Objective: Behavioral and psychological symptoms of dementia (BPSD) are among the most challenging aspects of Alzheimer disease for patients and their families. Previous studies have found associations between informant‐reported retrospective personality and BPSD; we test whether prospective, self‐reported personality predicts who will experience these symptoms. Methods: Deceased participants from the Health and Retirement Study who had evidence of cognitive impairment at the end of life (N = 1988) were selected to examine whether self‐reported five‐factor model personality traits, measured up to 8 years before death, were associated with proxy‐reported BPSD. Results: Neuroticism was associated with increased risk of the 7 BPSD: got lost in familiar places, wandered off, were not able to be left alone, experienced hallucinations, suffered from depression, had periodic confusion, and an uncontrolled temper. These associations were not moderated by age, gender, race, or education. Conscientiousness was associated with fewer symptoms overall and especially with lower risk of getting lost in familiar places and not being able to be left alone. Conclusions: The present research indicates that self‐reported personality, particularly Neuroticism, is associated prospectively with risk for a wide range of behavioral symptoms for individuals who had cognitive impairment at the end of life. The use of self‐reported personality traits can help aid in identifying who is most at risk for behavioral symptoms. Such information may be useful for nonpharmacological interventions tailored to the individual's personality to reduce the prevalence and burden of these BPSD.